2007
DOI: 10.1097/jto.0b013e31802bafb6
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Postoperative Respiratory Infections in Lung Cancer Surgery

Abstract: Lung cancer patients with advanced age, low FEV1%, advanced pathologic stage, or induction therapy had a risk for pneumonia after lung cancer surgery. Postoperative empyema was associated with advanced age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
56
2
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 17 publications
(22 reference statements)
4
56
2
4
Order By: Relevance
“…Similar to our study, Iwamoto et al found that patients older than 65 years who underwent thoracic surgery were associated with the highest incidence of pneumonia (10). Shiono et al reported that age older than 75 years was an independent significant risk factor for POP (8). However, the observation of increased POP risk with advanced age showed contrary to the findings to the Schussler et al study (14).…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Similar to our study, Iwamoto et al found that patients older than 65 years who underwent thoracic surgery were associated with the highest incidence of pneumonia (10). Shiono et al reported that age older than 75 years was an independent significant risk factor for POP (8). However, the observation of increased POP risk with advanced age showed contrary to the findings to the Schussler et al study (14).…”
Section: Discussioncontrasting
confidence: 56%
“…However, statistical significance was not observed (P>0.05) in multivariate analyses. The observation of our study was consistent with the findings of some reports (6,7), while disagreed with the findings of Shiono et al (8), which confirmed an increased risk of POP for cancer stages ≥III compared to stages I/II. Although statistical significance was not reached, we could still find the proportion of patients with POP in stages II/ III to be higher than stages I.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…However, this result has given rise to new questions: did prolongation of the drainage duration lead to empyema, or was drainage duration prolonged because of the development of empyema? Shiono et al reported that advanced age was a risk factor in development of empyema [17]. Although no statistical significance was found in analysis of the age factor, empyema development was more common in elderly cases.…”
Section: Discussionmentioning
confidence: 99%
“…Our work showed that ages, lymphocyte counts, smoking histories, histories of chronic bronchitis, operation modes and postoperative extubation time were significantly associated with pulmonary infection. Schussler (9) determined that postoperative pneumonia after lung resection developed in 25% of patients, and others also have demonstrated that elderly patients tend to develop respiratory infections after thoracic surgery (11,12). It was demonstrated, by multivariate analysis, that lung cancer patients of advanced ages, in particular those 75 years of age and older, was a high-risk group for postoperative pneumonia (12).…”
Section: Discussionmentioning
confidence: 99%